2012
DOI: 10.1097/scs.0b013e31824dbbb0
|View full text |Cite
|
Sign up to set email alerts
|

Tanzer Group IIB Constricted Ear Repair With Helical Advancement and Superior Auricular Artery Chondrocutaneous Flap

Abstract: Constricted ear deformity was first described by Tanzer and classified it into 3 groups according to the degree of constriction. The group IIB deformity involves the helix, scapha, and antihelical fold. The height of the ear is sharply reduced, and the soft tissue envelope is not sufficient to close the cartilage framework after expansion and reshaping.This study describes expanding the cartilage and increasing the height by advancing the helical root superiorly and repairing the skin-cartilage defect with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…It was reported that if the difference in height is less than 1 cm, it is considered a mild deformity, but if it is more than 2 cm, it is considered a severe deformity. 19 The aim in reconstructing Tanzer IIB constricted ears is extending both the tight skin cover and cartilage available to reconstruct the upper pole of ear. 18 The reconstructive techniques for group IIB deformity include (1) refashioning the original cartilage and/or grafting, (2) extending the skin cover with flaps, and (3) procedures that correct prominence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that if the difference in height is less than 1 cm, it is considered a mild deformity, but if it is more than 2 cm, it is considered a severe deformity. 19 The aim in reconstructing Tanzer IIB constricted ears is extending both the tight skin cover and cartilage available to reconstruct the upper pole of ear. 18 The reconstructive techniques for group IIB deformity include (1) refashioning the original cartilage and/or grafting, (2) extending the skin cover with flaps, and (3) procedures that correct prominence.…”
Section: Discussionmentioning
confidence: 99%
“…18 The reconstructive techniques for group IIB deformity include (1) refashioning the original cartilage and/or grafting, (2) extending the skin cover with flaps, and (3) procedures that correct prominence. 19 Stephenson 7 performed radial incisions to the existing cartilage to extend the cartilage in a fanlike manner. This is similar to what was done in the current study, as radial incisions were done to release the constricted concha to release the narrow intertragal notch, which have a positive impact on the patient's satisfaction with the conchal subunit.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, patients’ subjective impressions are important in the evaluation of outcomes, with satisfaction in appearance and symmetry being the most often assessed. [ 5 , 8 ] Braun et al [ 13 , 14 ] and Marone et al [ 13 , 14 ] utilized the Glasgow Benefit Inventory, a comprehensive measurement of the benefits of otorhinolaryngology involving motion, physical health, learning, vitality, and other psychosocial factors, to detect changes in the health status of patients. Woo et al [ 4 ] reported a quantized measurement of procedural pain, degree of improvement, and overall satisfaction survey.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys of satisfaction, observed symmetry, and appearance were often applied as subjective methods, with anthropometry of the auricle as the objective method. [ 5 , 8 , 9 ] However, these subjective evaluation methods were not all-inclusive and lacked specificity. Objective parameters are mostly measured by calipers and rulers, using the vertical height of the auricle (VHA) as the main index.…”
Section: Introductionmentioning
confidence: 99%
“…These latter defects are characterized by a short helical length and upper antihelical and Correction of microtia with constriction features using a superficial temporal fascial flap combined with a rib cartilage graft scaphal deficiencies and require supplemental skin for correction. Although various surgical correction methods have been reported as ways to resolve these deformities [2][3][4][5][6][7][8][9][10][11][12][13][14], no consensus has been reached regarding the most appropriate method. As the severity of a constricted ear deformity and the shape of the intact ear vary among individuals, diverse approaches to reconstruction that consider both the ear position and shape are needed to achieve symmetry.…”
Section: Introductionmentioning
confidence: 99%